Relationship Between Unhappy Musicians, Resistance Toward Innovation and Uncreative Music Products: Psychological Security as Moderator - Liang, Wei; Akhter, Shamim; Kumar, Tribhuwan (Frontiers in Psychology, 2022)
Recently, uncreative music products have become a global issue due to the unhappy musicians and resistance to innovation that needs researchers’ focus. The present article explores the impact of unhappy musicians and resistance to innovation on uncreative music products in Malaysia. The present article also investigates the moderating role of psychological security among the relationships of unhappy musicians, resistance to innovation and uncreative music products in Malaysia. The present study has applied the questionnaire method to gather the primary data from the selected respondents. The researchers have also applied the smart-PLS to check the nexus among constructs and test the hypotheses. The results revealed that unhappy musicians and resistance to innovation have a significant and positive linkage with uncreative music products in Malaysia. The results also exposed that psychological security significantly moderates the linkage among unhappy musicians, resistance to innovation and uncreative music products in Malaysia. Thus, this study guides the regulators to develop the regulations to reduce the unhappiness among musicians and motivation to adopt innovation to increase the creative music product in Malaysia.